Investigation of the anti-inflammatory effects of native potential probiotics as supplementary therapeutic agents in an in-vitro model of inflammation - Shadi Aghamohammad; Amin Sepehr; Seyedeh Tina Miri; Saeideh Najafi; Mohammad R. Pourshafie; Mahdi Rohani (BMC, 2023)
Abstract Background IBD is considered an inflammatory disease with abnormal and exaggerated immune responses. To control the symptoms, different theraputic agents could be used, however, utilizing the agents with the least side effects could be important. Probiotics as beneficial microorganisms are one of the complementory theraputic agents that could be used to modulate inflammatory signaling pathways. In the current study, we aimed to identify the precise molecular effects of potential probiotics on signaling pathways involved in the development of inflammation. Methods A quantitative real-time polymerase chain reaction (qPCR) assay was used to analyze the expression of JAK /STAT (JAK1, JAK2, JAK3, TYK2, STAT1, STAT2, STAT3, STAT4, STAT5 and STAT6) and inflammatory genes (NEMO, TIRAP, IRAK, and RIP) after the HT -29 cell line treatment with the sonicated pathogens and potential probiotics. A cytokine assay was also used to evaluate IL -6 and IL -1β production after potential probiotic treatment. Results The potential probiotic cocktail downregulated the JAK genes and TIRAP, IRAK4, NEMO, and RIP genes in the NF-kB pathway compared with cells that were treated with sonicated gram negative pathogens. The expression of STAT genes was different after potential probiotic treatment. The production of IL -6 and IL -1β decreased after potential probiotic treatment. Conclusions Considering the importance of controlling the symptoms of IBD to improve the life quality of the patients, using probiotic could be crucial. In the current study the studied native potential probiotic cocktails showed anti-inflammatory effects via modulation of JAK /STAT and NF-kB signaling pathways. This observation suggests that our native potential probiotics consumption could be useful in reducing intestinal inflammation.